Retrograde intrarenal surgery technique without using fluoroscopy and access sheet in the treatment of kidney stones - Firdolas, Fatih; Pirincci, Necip; Ozan, Tunc; Karakeci, Ahmet; Orhan, Irfan (Tubitak Scientific & Technological Research Council Turkey, 2019)
Background/aim: In this study, we aimed to present our results on single-guidewire flexible ureteroscopy and retrograde intrarenal surgery without fluoroscopy and an access sheet, and to evaluate the efficacy and safety of this procedure retrospectively. Material and methods: Our routine technique can be described as the evaluation of the ureter using a semirigid ureterorenoscope (URS), leading in the guidewire through the semirigid URS, pulling the semirigid URS back, inserting the flexible URS with the aid of the guidewire, inserting the laser probe through the flexible URS, and performing laser lithotripsy. Results: Our study included 400 male and 198 female patients with a mean age of 36.8 +/- 16 (14-80) years. The mean stone size was 8.7 +/- 4 (8-20) mm, and the mean operation time was 56 (32-106) min. Postoperative fever was observed in 24 (4%) of the patients, and 30 (5%) patients had hematuria as a minor complication. A stone-free status was observed in 466 (78%) patients, while 102 (17%) patients had clinically insignificant minor stone fragments and 30 patients had clinically significant stone residue. Conclusion: The retrograde intrarenal surgery procedure using only a guidewire without fluoroscopy and an access sheet in the treatment of kidney stones is technically safe and effective.
Keywords: Kidney stone; fluoroscopy; retrograde intrarenal surgery